2006
DOI: 10.1007/s11154-006-9006-0
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the diagnosis of osteoporosis: T-scores vs fractures

Abstract: The development of bone mineral densitimometry methodologies, especially central dual energy X-ray absorptiometry (DXA) methods have allowed this quantitative tool to be used to diagnose osteoporosis before the first fragility fracture has occurred. The World Health Organization osteoporosis working group set the stage for the BMD cut-off criteria development. The wide application of DXA has brought the treatment of osteoporosis to the primary care level, a very necessary step if this increasingly prevalent di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 101 publications
1
41
0
4
Order By: Relevance
“…As a result, older patients with fragility fractures who did not have osteoporosis, as defined by the World Health Organization criteria, may not have received treatment. 18 Our study supports the concept that bone mineral density captures only one aspect of fracture risk, namely the quantity of bone, and that other factors that may influence bone strength or the risk of falls are also contributors to fracture risk. For example, prospective studies have consistently demonstrated that clinical risk factors such as age, prior fracture, a family history of osteoporosis and corticosteroid use contribute to fracture risk, independent of bone density as determined by absorptiometry.…”
supporting
confidence: 83%
“…As a result, older patients with fragility fractures who did not have osteoporosis, as defined by the World Health Organization criteria, may not have received treatment. 18 Our study supports the concept that bone mineral density captures only one aspect of fracture risk, namely the quantity of bone, and that other factors that may influence bone strength or the risk of falls are also contributors to fracture risk. For example, prospective studies have consistently demonstrated that clinical risk factors such as age, prior fracture, a family history of osteoporosis and corticosteroid use contribute to fracture risk, independent of bone density as determined by absorptiometry.…”
supporting
confidence: 83%
“…Presence of osteoporosis was defined following well-established criteria 20,21 and the presence of bone sclerosis-as assessed by skeletal X-ray survey and/or computed tomography-scanwas also recorded. Skin biopsy was performed in all cases with cutaneous lesions.…”
Section: Diagnostic Work-up For Mastocytosismentioning
confidence: 99%
“…units relative to young adult men (T-score) and relative to age-matched men (Z-score). According to World Health Organization criteria, a normal BMD is defined as a T-score greater than K1 S.D.s, osteopenia as a T-score between K1 and K2.5, and osteoporosis as a T-score of K2.5 or less (Miller 2006).…”
Section: Bmd Measurementsmentioning
confidence: 99%
“…Comparison of the BMDs, T-scores, and Z-scores of the hormone-naive and ADT-treated patients According to new guidelines, osteoporosis can be diagnosed when DXA of the lumbar spine, total hip, or femoral neck yields a T-score of K2.5 or less (Miller 2006). Therefore, we measured the BMD at these three sites in this study.…”
Section: Patient Characteristicsmentioning
confidence: 99%